Bodies of the State fiscal service of Ukraine as a subject of information legal relations - Lytvyn, Nataliia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The subjects of information legal relations are investigated in the scientific article. The authorities of the State Fiscal Service of Ukraine (next – SFS of Ukraine) as a subject of information legal relations are separately considered. It is noted that the participation of the subjects of power authorities in information legal relations has its peculiarities, the main of which is the fact that the main prerequisite for the participation of such a subject in the information legal relationship is his competence.